RESPONS SISWA TERHADAP MEDIA PEMBELAJARAN APLIKASI CAMTASIA DENGAN METODE KONTEKSTUAL PADA PEMBELAJARAN TEKS PROSEDUR KELAS VII SMP - Hasan Zuhamad Zulfiqri; Teti Sobari; Yeni Rostikawati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The real problems in the field found that the learning activities of this procedure text are still less effective in using learning media in general, seen from the results of observations by interviewing students that students feel bored with learning procedure text because the learning media used only use textbooks that contain text and theory only. The purpose of this study was to determine the response of students after applying video learning media and applying contextual learning methods which are learning concepts to help teachers connect material with applications in everyday life. The research method used is descriptive quantitative, based on the research that has been done, the author uses a questionnaire instrument to find out the students' response to the procedure text material using video-based learning media, the research subject is SMPN 3 BATUJAJAR students, the population in this study are class VII A students with a total of 25 students, the following student questionnaire results get a percentage of 75.2%, thus it can be concluded that the application of learning methods and camtasia application learning media gets a positive response from students.